Menurunkan Kecemasan pada Anak yang Dirawat di Rumah Sakit dengan Teknik Menggambar dan Mewarnai - Jawiah Jawiah; Rehana Rehana; Umar Hasan MartaDinata; Yeny Elviani; Jenny Amelia (Journal of Telenursing (JOTING), 2023)
This study aims to reduce anxiety in hospitalized children through drawing and coloring techniques. Drawing and coloring aim to make children happy and fearless and can be used as entertainment when hospitalized. This research method uses a descriptive design as a case study with a nursing process approach consisting of assessment, nursing diagnosis, planning (intervention), implementation (implementation), evaluation, and documentation. Data collection techniques using observation, interviews, and filling out case study instruments for three days in the treatment room. The results showed that the implementation of nursing given in the form of drawing and coloring distraction techniques affected reducing anxiety experienced by pediatric patients during hospitalization. The anxiety score decreased significantly after applying the drawing and coloring distraction methods. In conclusion, drawing and coloring distraction techniques can reduce anxiety in children who experience hospitalization; anxiety scores decrease after being given picture and coloring traction techniques Keywords: Anxiety, Drawing and Coloring Techniques